A Review on the Application of Peening Processes for Surface Treatment - Azmir, Azhari; S., Sulaiman; A. K., Prasada Rao (IOP Publishing, 2016)
In today’s practice, mechanical surface treatments have been widely applied particularly in the automotive and aerospace industries. It was realized that the failure due to fatigue depends on many factors, and very often it develops from particular surface areas of engineering parts. So, it seems possible to improve the fatigue strength of metallic components by the application of suitable mechanical surface strengthening processes. Peening processes are widely employed in industry for inducing compressive stresses on the metallic surfaces. The present work discusses the basic concepts and their applications of main peening processes namely the shot peening and the laser shock peening. Also, a recently introduced liquid jet peening is discussed.